Through-hole type ultra-high molecular weight polyethylene fiber as well as preparation method and application thereof
Ultra-high molecular weight polyethylene fibers with oil conduction through holes were prepared by etching method, which solved the problem of low oil absorption rate of the fiber and achieved rapid absorption and diffusion prevention effect.
Patent Information
- Application Number
- CN202311159811.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-08
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-09-08
AI Technical Summary
Ultra-high molecular weight polyethylene fiber has low oil absorption rate and is difficult to effectively apply in the field of offshore oil removal.
Ultra-high molecular weight polyethylene fibers with oil conduction through holes were prepared by etching method, and concave holes were formed by dissolving pre-placed calcium carbonate particles in the drafting wire stage, and oil conduction through holes were expanded by ultra-fold stretching.
By forming oil conduction through holes, the oil absorption capacity of the fiber is improved, so that the leaked oil can be quickly absorbed into the fiber, effectively preventing oil leakage and achieving excellent oil absorption effect.
Smart Images

Figure BDA0004440151640000141
Abstract
Description
Technical Field
[0001] The present invention relates to the field of high-performance fibers, and in particular to a through-hole ultra-high molecular weight polyethylene fiber, a manufacturing method thereof and applications thereof. Background Art
[0002] Oil spills at sea are extremely harmful to the marine ecology. How to quickly remove the oil spill and prevent it from spreading has always been a difficult problem. Ultra-high molecular weight polyethylene fibers have a density lower than that of water and can float on the water surface. From this perspective, they should be an excellent choice for oil removal. However, the molecular chain structure of ultra-high molecular weight polyethylene is dense and regular, and its low oil absorption rate makes it difficult to use in the field of offshore oil removal. This patent uses an etching method to prepare ultra-high molecular weight polyethylene fibers with oil-conducting through holes and make them into oil-absorbing felt to solve this problem. Summary of the invention
[0003] The invention aims to provide a felt with oil-conducting through-hole fibers, which can float on seawater and quickly absorb oil, thereby solving the problems of rapid diffusion and difficulty in collecting oil leaks.
[0004] Specifically, the present invention relates to the following aspects.
[0005] 1. A method for producing a through-hole ultra-high molecular weight polyethylene fiber, comprising the following steps:
[0006] 1) mixing ultra-high molecular weight polyethylene, acid-soluble inorganic particles and a solvent to prepare a spinning solution,
[0007] 2) extruding the spinning solution to form a spinning fine stream,
[0008] 3) removing at least a portion (e.g., at least 50 wt%, preferably at least 70 wt%, at least 80 wt%, at least 90 wt%, at least 95 wt% or at least 97 wt%) of the solvent from the spinning stream to obtain dry raw fibers,
[0009] 4) stretching the dry precursor in two or more stages (such as 2-10 or 2-6 stages), and while one or more of these stages are being carried out, spraying an acidic liquid on the dry precursor to dissolve the acid-soluble inorganic particles to obtain the through-hole type ultra-high molecular weight polyethylene fiber.
[0010] 2. The manufacturing method described in any of the above or below aspects, wherein in step 1), relative to 100 parts by weight of the ultra-high molecular weight polyethylene, the amount of the acid-soluble inorganic particles used is 0.5-50 parts by weight (preferably 1-10 parts by weight), and the amount of the solvent used is 500-1000 parts by weight (preferably 8-20 parts by weight).
[0011] 3. The production method described in any of the preceding or following aspects, wherein in step 1), the solvent is selected from at least one of naphthalene, decalin, tetralin, kerosene, xylene, toluene, petroleum fractions, halogenated hydrocarbons, cycloalkanes, and cycloolefins, preferably decalin.
[0012] 4. The manufacturing method described in any of the preceding or following aspects, wherein in step 1), the average particle size of the acid-soluble inorganic particles is 0.02-20 μm (preferably 0.5-5 μm), the acid-soluble inorganic particles are selected from at least one of calcium carbonate, sodium carbonate, sodium bicarbonate, and magnesium carbonate (preferably calcium carbonate, especially light calcium carbonate), and the viscosity-average molecular weight of the ultra-high molecular weight polyethylene is 1 million to 9 million (preferably 3 million to 5 million).
[0013] 5. The production method described in any one of the preceding or following aspects, wherein in step 1), the acid-soluble inorganic particles are mixed with the solvent and then mixed with the ultra-high molecular weight polyethylene.
[0014] 6. The manufacturing method described in any of the above or below aspects, wherein in step 1), the difference between the relative density of the ultra-high molecular weight polyethylene and the bulk density of the acid-soluble inorganic particles is 0.20 g / cm3 or more (preferably 0.25-0.60 g / cm3).
[0015] 7. The manufacturing method described in any of the above or the following aspects, wherein in step 2), stretching exists or does not exist, the extrusion temperature is 150-250°C (preferably 170-190°C), and the spinneret micropore diameter is 0.1-5mm (preferably 0.5-1.5mm); when stretching exists, the stretching ratio is 0-50 (preferably 2-20).
[0016] 8. The manufacturing method according to any one of the preceding or following aspects, wherein in step 3), the spinning stream is cooled to obtain gel filaments, and then at least a portion of the solvent is removed by evaporation and / or extraction.
[0017] 9. The manufacturing method described in any of the above or the following aspects, wherein the cooling operating conditions include: with or without stretching, the cooling temperature is -50-100°C (preferably 20-50°C); when stretching is present, the stretching ratio is 1-10 (preferably 2-5).
[0018] 10. The manufacturing method described in any of the above or the following aspects, wherein the operating conditions of the evaporation include: with or without stretching, the evaporation temperature is 0.5-10°C (preferably 1-5°C) higher than the solvent flash temperature; when stretching is present, the stretching ratio is 1-10 (preferably 2-5), or, the operating conditions of the extraction include: with or without stretching, the extractant is a volatile hydrocarbon solvent (preferably selected from at least one of xylene and heptane), the extraction temperature is 10-150°C (preferably 40-90°C); when stretching is present, the stretching ratio is 1-10 (preferably 2-5).
[0019] 11. The manufacturing method described in any of the preceding or following aspects, wherein in step 4), the stretching operating conditions include: 1-10 stretching sections (preferably 2-5), a stretching temperature of 90-170°C (preferably 130-150°C), and a stretching ratio of 2-500 (preferably 4-250).
[0020] 12. The manufacturing method described in any of the above or the following aspects, wherein in step 4), the dry raw silk is first pre-stretched, and then the dry raw silk is further stretched (called post-stretching) in one or more (such as 1-9 or 1-5) stages, and the spraying is carried out while the post-stretching is being carried out.
[0021] 13. The manufacturing method described in any of the above or below aspects, wherein the stretching ratio of the pre-stretching is 1-10 (preferably 2-5), and the stretching ratio (total) of the post-stretching is 2-50 (preferably 5-20).
[0022] 14. The manufacturing method described in any of the preceding or following aspects, wherein in step 4), the acidic liquid comprises at least one acid selected from inorganic acids and organic acids, and a solvent, wherein the pH value of the acidic bath is ≤6 (preferably 2-3).
[0023] 15. The manufacturing method described in any of the preceding or following aspects, wherein the inorganic acid is selected from at least one of sulfuric acid, hydrochloric acid, hydrofluoric acid, boric acid, and phosphoric acid (preferably selected from at least one of sulfuric acid and hydrochloric acid), the organic acid is selected from at least one of acetic acid, tartaric acid, oxalic acid, malic acid, citric acid, ascorbic acid, sulfonic acid, sulfinic acid, and sulfuric acid (preferably selected from at least one of acetic acid and citric acid), and the solvent is selected from at least one of glacial acetic acid, ethanol, and water, preferably water.
[0024] 16. The manufacturing method described in any of the preceding or following aspects, wherein in step 4), the spraying operating conditions include: spraying pressure 0.1-10MPa (preferably 0.5-1MPa), spraying time 1-120min (preferably 10-30min), spraying temperature 0-100℃ (preferably 30-50℃).
[0025] 17. The manufacturing method described in any of the above or the following aspects further includes the steps of washing, extruding, curling and shortening the through-hole ultra-high molecular weight polyethylene fiber.
[0026] 18. The manufacturing method described in any one of the preceding or following aspects, wherein an oil is applied to the dry raw yarn before the post-stretching is performed.
[0027] 19. The method of any one of the above or the following aspects, wherein at least one of glycerol ester, mineral oil, lauryl alcohol polyoxyethylene ether and antistatic agent, preferably glycerol ester, is used in an amount of 0-10% (preferably 0.1-3%).
[0028] 20. The method according to any one of the preceding or following aspects, wherein in step 3), at least a portion of the solvent is removed from the spinning stream by evaporation.
[0029] 21. The manufacturing method described in any of the above or the following aspects, wherein in step 3), the operating conditions of the evaporation include: with or without stretching, the evaporation temperature is 0.5-10°C (preferably 1-5°C) higher than the solvent flash temperature; when stretching is present, the stretching ratio is 1-10 (preferably 2-5).
[0030] 22. A through-hole ultra-high molecular weight polyethylene fiber obtained by the production method described in any one of the preceding or following aspects.
[0031] 23. The through-hole ultra-high molecular weight polyethylene fiber described in any of the above or below aspects has a porosity of 1% to 50% (preferably 20% to 30%) and a fiber strength of 1-35 cN / dtex (preferably 5-15 cN / dtex).
[0032] 24. A through-hole type ultra-high molecular weight polyethylene staple fiber obtained by the manufacturing method described in any of the above or below aspects, with a curl of at least 1 / 25mm (preferably 3-5 / 25mm) and a length of at least 3mm (preferably 38-78mm).
[0033] 25. A fabric comprising the through-hole type ultra-high molecular weight polyethylene fiber described in any one of the preceding or following aspects or the through-hole type ultra-high molecular weight polyethylene short fiber described in any one of the preceding or following aspects.
[0034] 26. The fabric described in any one of the preceding or following aspects further comprises at least one other fiber selected from natural plant fibers, natural animal fibers, artificial regenerated fibers, synthetic fibers and inorganic fibers.
[0035] 27. Use of the fabric described in any of the preceding or following aspects as an absorbent material (especially oil absorbent felt).
[0036] Technical Effects
[0037] The present invention adopts an etching method to prepare ultra-high molecular weight polyethylene fibers with oil-conducting holes. In the drawing stage, pre-set calcium carbonate particles are dissolved to form concave holes. Then, after super-multiple stretching, the concave holes are stretched radially to form oil-conducting holes. The fiber is curled, shaped, and cut short, and then air-laid and pressed into a felt. The prepared felt can float on the sea, and the leaked oil can be quickly absorbed into the fiber through the capillary effect and is not easy to escape. The ultra-high molecular weight polyethylene felt can float on the water surface, effectively covering the oil leakage area to prevent the oil leakage from spreading. The fiber surface and the inside are covered with oil-conducting holes. Through the wicking effect, the leaked oil can be quickly absorbed into the fiber and stored to prevent back leakage, achieving an excellent oil absorption effect. The product made by the air-laid process has more fluffy tissues and larger pores than the traditional combing process, which is convenient for oil absorption and oil retention. DETAILED DESCRIPTION
[0038] The specific embodiments of the present invention are described in detail below, but it should be pointed out that the protection scope of the present invention is not limited by these specific embodiments, but is determined by the claims in the appendix.
[0039] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definitions in this specification shall prevail.
[0040] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.
[0041] In the context of the present invention, all numerical values for parameters (eg amounts or conditions) are to be understood as being modified in all instances by the term "about", regardless of whether "about" actually appears before the numerical value.
[0042] In the context of the present invention, the method of measuring porosity is mercury porosimetry.
[0043] In the context of the present invention, the fiber strength is measured according to GB / T 19975.
[0044] In the context of the present invention, the method of measuring the average particle size is laser light scattering.
[0045] In the context of the present invention, the oil absorption rate is measured by weighing method. Cut oil-absorbing felt blocks of the same weight W0, immerse them in standard oil for 5 minutes, take them out to drain and absorb the surface grease with paper towels, and weigh W1. (W1-W0) / W0×100=oil absorption rate %.
[0046] Unless otherwise specified, all percentages, parts, ratios, etc. mentioned in this specification are based on weight and pressure is gauge pressure.
[0047] In the context of the present invention, any two or more embodiments or aspects of the present invention may be arbitrarily combined, and the technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.
[0048] According to one embodiment of the present invention, a method for manufacturing a through-hole ultra-high molecular weight polyethylene fiber is provided. According to the present invention, the so-called "through-hole ultra-high molecular weight polyethylene fiber" refers to an ultra-high molecular weight polyethylene fiber having a through hole from one end to the other end on its cross section.
[0049] According to one embodiment of the present invention, the method for manufacturing the through-hole type ultra-high molecular weight polyethylene fiber comprises the following steps:
[0050] 1) ultra-high molecular weight polyethylene, acid-soluble inorganic particles and a solvent are mixed to prepare a spinning solution,
[0051] 2) extruding the spinning solution to form a spinning fine stream,
[0052] 3) removing at least a portion (e.g., at least 50 wt%, preferably at least 70 wt%, at least 80 wt%, at least 90 wt%, at least 95 wt% or at least 97 wt%) of the solvent from the spinning stream to obtain dry raw fibers,
[0053] 4) stretching the dry precursor in two or more stages (such as 2-10 or 2-6 stages), and while one or more of these stages are being carried out, spraying an acidic liquid on the dry precursor to dissolve the acid-soluble inorganic particles to obtain the through-hole type ultra-high molecular weight polyethylene fiber.
[0054] According to one embodiment of the present invention, in step 1), the amount of the acid-soluble inorganic particles is 0.5-50 parts by weight (preferably 1-10 parts by weight) relative to 100 parts by weight of the ultra-high molecular weight polyethylene.
[0055] According to one embodiment of the present invention, in step 1), the amount of the solvent used is 500-1000 parts by weight (preferably 8-20 parts by weight) relative to 100 parts by weight of the ultra-high molecular weight polyethylene.
[0056] According to one embodiment of the present invention, in step 1), the solvent is selected from at least one of naphthalene, decalin, tetralin, kerosene, xylene, toluene, petroleum fractions, halogenated hydrocarbons, cycloalkanes, and cycloolefins, preferably decalin.
[0057] According to one embodiment of the present invention, in step 1), the average particle size of the acid-soluble inorganic particles is 0.02-20 μm (preferably 0.5-5 μm).
[0058] According to one embodiment of the present invention, in step 1), the acid-soluble inorganic particles are not particularly limited, and may be any inorganic particles that can react chemically with an acid (particularly hydrochloric acid or a hydrochloric acid aqueous solution) to be converted into (water) soluble compounds, and in particular may be at least one particle selected from calcium carbonate, sodium carbonate, sodium bicarbonate and magnesium carbonate, preferably calcium carbonate particles, in particular light calcium carbonate particles (whose bulk density is generally 0.50-0.70 g / cm 3 ).
[0059] According to one embodiment of the present invention, in order to make the technical effect of the present invention more excellent, in step 1), the difference (absolute value) between the relative density of the ultra-high molecular weight polyethylene and the bulk density of the acid-soluble inorganic particles is 0.20 g / cm 3 Above (preferably 0.25-0.60g / cm 3 ). Preferably, the relative density of the ultra-high molecular weight polyethylene is greater than the bulk density of the acid-soluble inorganic particles. It is known that the relative density of the ultra-high molecular weight polyethylene is generally 0.90-0.97 g / cm 3 .
[0060] According to one embodiment of the present invention, the viscosity-average molecular weight of the ultra-high molecular weight polyethylene is 1 million to 9 million (preferably 3 million to 5 million).
[0061] According to one embodiment of the present invention, in step 1), the acid-soluble inorganic particles are mixed with the solvent and then mixed with the ultra-high molecular weight polyethylene.
[0062] According to one embodiment of the present invention, in step 2), there is stretching or there is no stretching, the extrusion temperature is 150-250°C (preferably 170-190°C), and the spinneret micropore diameter is 0.1-5mm (preferably 0.5-1.5mm). When there is stretching, the stretching ratio is 0-50 (preferably 2-20).
[0063] According to one embodiment of the present invention, in step 3), at least a portion of the solvent is removed from the spinning stream by evaporation (direct evaporation desolvation method). According to the present invention, except for the following clear operating conditions, there is no other limitation on the direct evaporation desolvation method, and it can be carried out in a manner conventionally known in the art. Here, the operating conditions of the evaporation include: with or without stretching, the evaporation temperature is 0.5-10°C (preferably 1-5°C) higher than the solvent flash temperature. When stretching is present, the stretching ratio is 1-10 (preferably 2-5).
[0064] According to one embodiment of the present invention, in step 3), the spinning stream is cooled to obtain gel filaments (gel spinning method), and then at least a portion of the solvent is removed by evaporation and / or extraction. According to the present invention, except for the following clear operating conditions, there is no other limitation for the gel spinning method, and it can be carried out in a conventional manner known in the art.
[0065] According to one embodiment of the present invention, the cooling operation conditions include: with or without stretching, the cooling temperature is -50-100°C (preferably 20-50°C). When stretching is present, the stretching ratio is 1-10 (preferably 2-5).
[0066] According to one embodiment of the present invention, the evaporation operation conditions include: with or without stretching, the evaporation temperature is 0.5-10°C (preferably 1-5°C) higher than the solvent flash temperature. When stretching is present, the stretching ratio is 1-10 (preferably 2-5).
[0067] According to one embodiment of the present invention, the operating conditions of the extraction include: with or without stretching, the extraction temperature is 10-150°C (preferably 40-90°C); when stretching is present, the stretching ratio is 1-10 (preferably 2-5). Here, the extractant is a volatile hydrocarbon solvent, preferably at least one selected from xylene and heptane.
[0068] According to one embodiment of the present invention, in step 4), the stretching operating conditions include: 1-10 stretching sections (preferably 2-5), a stretching temperature of 90-170°C (preferably 130-150°C), and a stretching ratio of 2-500 (preferably 4-250).
[0069] According to one embodiment of the present invention, an oil is applied to the dry raw silk before the stretching and / or between any two stages. Alternatively, an oil is applied to the dry raw silk before the post-stretching and / or between any two stages (if any) of the post-stretching. According to the present invention, since the surface of the fiber to which the peracid-soluble inorganic particles are added is rough, it is easy to wear and tear during the subsequent drawing process, causing powder loss or fiber surface damage, and generally requires oil film protection.
[0070] According to one embodiment of the present invention, the oil is selected from at least one of glycerol ester, mineral oil, lauryl alcohol polyoxyethylene ether, and antistatic agent, preferably glycerol ester. Here, the amount of the oil is 0-10% (preferably 0.1-3%).
[0071] According to one embodiment of the present invention, in step 4), the dry raw yarn is first pre-stretched, and then further stretched (called post-stretching) in one or more stages (such as 1-9 or 1-5), and the spraying is performed while the post-stretching is performed.
[0072] According to one embodiment of the present invention, the stretching ratio of the pre-stretching is 1-10 (preferably 2-5), and the stretching ratio (total) of the post-stretching is 2-50 (preferably 5-20).
[0073] According to one embodiment of the present invention, in step 4), the acidic liquid comprises at least one acid selected from inorganic acids and organic acids, and a solvent.
[0074] According to one embodiment of the present invention, the pH value of the acidic bath is ≤6 (preferably 2-3).
[0075] According to one embodiment of the present invention, the inorganic acid is selected from at least one of sulfuric acid, hydrochloric acid, hydrofluoric acid, boric acid and phosphoric acid (preferably selected from at least one of sulfuric acid and hydrochloric acid).
[0076] According to one embodiment of the present invention, the organic acid is selected from at least one of acetic acid, tartaric acid, oxalic acid, malic acid, citric acid, ascorbic acid, sulfonic acid, sulfinic acid, and sulfuric acid (preferably selected from at least one of acetic acid and citric acid).
[0077] According to one embodiment of the present invention, the solvent is selected from at least one of glacial acetic acid, ethanol and water, preferably water.
[0078] According to one embodiment of the present invention, in step 4), the spraying operating conditions include: spraying pressure 0.1-10 MPa (preferably 0.5-1 MPa), spraying time 1-120 min (preferably 10-30 min), and spraying temperature 0-100°C (preferably 30-50°C).
[0079] According to one embodiment of the present invention, the manufacturing method further comprises the steps of washing, extruding, curling and shortening the through-hole type ultra-high molecular weight polyethylene fiber.
[0080] According to one embodiment of the present invention, it also relates to a through-hole ultra-high molecular weight polyethylene fiber, which is obtained by the manufacturing method described in any one of the preceding or following aspects of this specification. According to the present invention, the through-hole ultra-high molecular weight polyethylene fiber has a porosity of 1% to 50% (preferably 20% to 30%) and a fiber strength of 1-35 cN / dtex (preferably 5-15 cN / dtex).
[0081] According to one embodiment of the present invention, there is also a through-hole type ultra-high molecular weight polyethylene staple fiber, which is obtained by the manufacturing method described in any one of the preceding or following aspects of this specification. According to the present invention, the through-hole type ultra-high molecular weight polyethylene staple fiber has a curl of at least 1 / 25mm (preferably 3-5 / 25mm) and a length of at least 3mm (preferably 38-78mm).
[0082] According to one embodiment of the present invention, a fabric is also provided, comprising the through-hole ultra-high molecular weight polyethylene fiber or the through-hole ultra-high molecular weight polyethylene short fiber described in any one of the preceding or following aspects of the present specification. The fabric is particularly suitable for use as an adsorbent material (especially oil-absorbing felt).
[0083] According to one embodiment of the present invention, the fabric further comprises at least one other fiber selected from natural plant fibers, natural animal fibers, artificial regenerated fibers, synthetic fibers and inorganic fibers.
[0084] Example
[0085] The present invention is further described in detail below using examples and comparative examples, but the present invention is not limited to these examples.
[0086] Example 1
[0087] The through-hole ultra-high molecular weight polyethylene fiber of this embodiment is obtained by the following process:
[0088] The acid-soluble inorganic particles are light calcium carbonate, and the difference between its bulk density and the relative density of ultra-high molecular weight polyethylene is 0.32 g / cm 3, with an average particle size of 2μm. After being evenly dispersed with the decahydronaphthalene solvent, it is mixed with ultra-high molecular weight polyethylene to form a swelling suspension. The molecular weight of ultra-high molecular weight polyethylene is 4.5 million. The mass ratio of ultra-high molecular weight polyethylene: calcium carbonate: decahydronaphthalene is 100:5:1300. The suspension is dissolved by screw shearing and extruded at 180°C and 8 times stretching to form a spinning fine flow. The diameter of the spinneret micropore is 1mm. The direct evaporation method is used to remove the solvent. The evaporation temperature is 3°C higher than the flash temperature of decahydronaphthalene, and the stretching ratio is 3. This step removes at least 95% of the solvent residue. Then it goes through 3 stretching sections, the stretching temperature is 140℃, the stretching ratio is 120, then it goes through 3 times pre-stretching and 8 times post-spinning total drafting, and at the same time it is sprayed with dilute hydrochloric acid (hydrochloric acid and water) with pH=2.5, the spraying pressure is 0.7MPa, the spraying time is 20min, the spraying temperature is 40℃, and then it is oiled by an oil tanker with an oiling rate of 0.5%, and finally the finished filament is formed. It is cleaned, extruded, curled and cut to obtain short fibers, which are pressed into oil-absorbing felt.
[0089] Example 2
[0090] The same as Example 1, except that the amount of calcium carbonate added was 0.6 parts by weight.
[0091] Example 3
[0092] Same as Example 1, except that the average particle size of calcium carbonate is 0.1 μm.
[0093] Example 4
[0094] Same as Example 1, except that the average particle size of calcium carbonate added is 10 μm.
[0095] Example 5
[0096] The same as Example 1, except that the amount of calcium carbonate added was 10 parts by weight.
[0097] Example 6
[0098] Similar to Example 1, calcium carbonate is not premixed with the solvent, but is directly mixed with the ultra-high molecular weight polyethylene and the solvent.
[0099] Example 7
[0100] Same as Example 1, except that the acid-soluble inorganic particles are magnesium carbonate, and the difference between its bulk density and the relative density of ultra-high molecular weight polyethylene is 0.70 g / cm 3 .
[0101] Example 8
[0102] Same as Example 1, except that the acid-soluble inorganic particles are heavy calcium carbonate, and the difference between its bulk density and the relative density of ultra-high molecular weight polyethylene is 0.15 g / cm3 .
[0103] Example 9
[0104] Same as Example 1, except that the molecular weight of the ultra-high molecular weight polyethylene is 5 million.
[0105] Example 10
[0106] Same as Example 1, except that the molecular weight of the ultra-high molecular weight polyethylene is 2.5 million.
[0107] Embodiment 11
[0108] The same as Example 1, except that the amount of decalin used is 2000 parts.
[0109] Example 12
[0110] Same as Example 1, except that the spinneret aperture is 2.0 mm.
[0111] Example 13
[0112] Same as Example 1, except that dilute sulfuric acid was used, pH=2.
[0113] Comparative Example 1
[0114] Compared with Example 1, light calcium carbonate is only replaced by sodium chloride.
[0115] Comparative Example 2
[0116] The same as Example 1, except that compared with Example 1, the diluted hydrochloric acid is sprayed first, and then 3 times pre-stretching and 8 times post-spinning total stretching are performed.
[0117] Comparative Example 3
[0118] The fiber is commercially available LY25 400D ultra-high molecular weight polyethylene fiber.
[0119] Comparative Example 4
[0120] The same as Example 1, except that the amount of calcium carbonate added was 60 parts by weight.
[0121] Comparative Example 5
[0122] Same as Example 1, except that the average particle size of calcium carbonate is 50 μm.
[0123] Comparative Example 6
[0124] The same as Example 1, except that before the direct evaporation method is used to remove the solvent, three stretching sections are carried out, the stretching temperature is 140°C, the stretching ratio is 120, and then 3 times pre-stretching and 8 times post-spinning total stretching are performed, and at the same time, it is sprayed with dilute hydrochloric acid (hydrochloric acid and water) with a pH of 2.5, the spraying pressure is 0.7MPa, the spraying time is 20min, and the spraying temperature is 40°C. This method cannot form finished silk.
[0125]
Claims
1. A method for producing a through-hole ultra-high molecular weight polyethylene fiber, comprising the following steps: 1) mixing ultra-high molecular weight polyethylene, acid-soluble inorganic particles and a solvent to prepare a spinning solution, 2) extruding the spinning solution to form a spinning fine stream, 3) removing at least a portion (e.g., at least 50 wt%, preferably at least 70 wt%, at least 80 wt%, at least 90 wt%, at least 95 wt% or at least 97 wt%) of the solvent from the spinning stream to obtain dry raw fibers, 4) stretching the dry precursor in two or more stages (such as 2-10 or 2-6 stages), and while one or more of these stages are being carried out, spraying an acidic liquid on the dry precursor to dissolve the acid-soluble inorganic particles to obtain the through-hole type ultra-high molecular weight polyethylene fiber.
2. The manufacturing method according to claim 1, wherein in step 1), the amount of the acid-soluble inorganic particles is 0.5-50 parts by weight (preferably 1-10 parts by weight) relative to 100 parts by weight of the ultra-high molecular weight polyethylene, and the amount of the solvent is 100-3000 parts by weight (preferably 400-2000 parts by weight).
3. The manufacturing method according to claim 1, wherein in step 1), the average particle size of the acid-soluble inorganic particles is 0.02-20 μm (preferably 0.5-5 μm), the acid-soluble inorganic particles are selected from at least one of calcium carbonate, sodium carbonate, sodium bicarbonate, and magnesium carbonate (preferably calcium carbonate, especially light calcium carbonate), and the viscosity-average molecular weight of the ultra-high molecular weight polyethylene is 1 million to 9 million (preferably 3 million to 5 million).
4. The production method according to claim 1, wherein in step 1), the acid-soluble inorganic particles are mixed with the solvent and then mixed with the ultra-high molecular weight polyethylene.
5. The manufacturing method according to claim 1, wherein in step 1), the difference between the relative density of the ultra-high molecular weight polyethylene and the bulk density of the acid-soluble inorganic particles is 0.20 g / cm 3 Above (preferably 0.25-0.60g / cm 3 ).
6. The manufacturing method according to claim 1, wherein in step 2), stretching is present or absent, the extrusion temperature is 150-250°C (preferably 170-190°C), and the spinneret micropore diameter is 0.1-5 mm (preferably 0.5-1.5 mm); when stretching is present, the stretching ratio is 0-50 (preferably 2-20).
7. The manufacturing method according to claim 1, wherein in step 4), the operating conditions of the stretching include: The number of stretching sections is 1-10 (preferably 2-5), the stretching temperature is 90-170° C. (preferably 130-150° C.), and the stretching ratio is 2-500 (preferably 4-250).
8. The manufacturing method of claim 1, wherein in step 4), the dry raw yarn is first pre-stretched, and then further stretched (called post-stretching) in one or more (such as 1-9 or 1-5) stages, and the spraying is performed while the post-stretching is performed.
9. The manufacturing method according to claim 8, wherein the stretching ratio of the pre-stretching is 1-10 (preferably 2-5), and the stretching ratio (total) of the post-stretching is 2-50 (preferably 5-20).
10. The manufacturing method according to claim 1, wherein in step 4), the acidic liquid comprises at least one acid selected from inorganic acids and organic acids, and a solvent, wherein the pH value of the acidic bath is ≤ 6 (preferably 2-3).
11. The production method according to claim 10, wherein the inorganic acid is selected from at least one of sulfuric acid, hydrochloric acid, hydrofluoric acid, boric acid, and phosphoric acid (preferably selected from at least one of sulfuric acid and hydrochloric acid), the organic acid is selected from at least one of acetic acid, tartaric acid, oxalic acid, malic acid, citric acid, ascorbic acid, sulfonic acid, sulfinic acid, and sulfuric acid (preferably selected from at least one of acetic acid and citric acid), and the solvent is selected from at least one of glacial acetic acid, ethanol, and water, preferably water.
12. The manufacturing method according to claim 1, wherein in step 4), the operating conditions of the spraying include: The spraying pressure is 0.1-10 MPa (preferably 0.5-1 MPa), the spraying time is 1-120 min (preferably 10-30 min), and the spraying temperature is 0-100° C. (preferably 30-50° C.).
13. The manufacturing method according to claim 1, further comprising the steps of washing, extruding, curling and shortening the through-hole ultra-high molecular weight polyethylene fiber.
14. A through-hole ultra-high molecular weight polyethylene fiber obtained by the manufacturing method according to claim 1, wherein the porosity is 1% to 50% (preferably 20% to 30%) and the fiber strength is 1-35 cN / dtex (preferably 5-15 cN / dtex).
15. A through-hole ultra-high molecular weight polyethylene staple fiber obtained by the manufacturing method described in claim 13, wherein the curl degree is at least 1 / 25mm (preferably 3-5 / 25mm) and the length is at least 3mm (preferably 38-78mm). 16 . A fabric comprising the through-hole type ultra-high molecular weight polyethylene fiber according to claim 14 or the through-hole type ultra-high molecular weight polyethylene short fiber according to claim 15 .
17. Use of the fabric according to claim 16 as an absorbent material (especially oil absorbent felt).
Citation Information
Patent Citations
Preparation method of porous active ultra-high molecular weight polyethylene fiber, polyethylene fiber and application of polyethylene fiber
CN112323158A
Manufacturing method of high strength polyethylene fiber
CN1590608A
Fine porous fiber
JP1997157944A
Polyolefin-based resin composition, method for producing porous film by using the composition, porous film, method for producing laminated porous film, laminated porous film, and separator for battery
JP2010195898A
Porous hollow fiber
US20130118981A1